Pengaruh Kualitas Pelayanan dan Harga, Terhadap Kepuasan Pelanggan di UD. Usaha Bersama Magepanda : (Study Kasus Pada Kecamatan Magepanda) - Irwanto Sale; Antonius Philipus Kurniawan; Walter Obon (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This study aims to determine the description and influence of service quality, price, and customer satisfaction at UD. Usaha Bersama Magepanda. Products and Prices on Customer Satisfaction both partially and simultaneously. The population in this study were consumers of UD. Usaha Bersama Magepanda, in Magepanda District, Sikka Regency. With an unlimited population, a sample of 100 people was taken. Data were collected through questionnaires and analyzed using Descriptive and Associative methods, namely multiple linear regression. Hypothesis testing was carried out through the F test and t test and the Determination Coefficient (R2). The results of the descriptive analysis showed that the Service Satisfaction variable was in the fairly good criteria, the Service Quality variable was in the good criteria, then the Price variable was in the good criteria. Partially, the service quality variable (X1) had a significant effect on the satisfaction variable (Y). Partially, the price variable (X2) did not have a significant effect on the satisfaction variable (Y). Together, the two independent variables, namely the service quality variable (X1) and price (X2), had a significant effect on customer satisfaction (Y). The magnitude of the contribution of the variables of Service Quality and Price, to Customer Satisfaction at UD. Usaha Bersama Magepanda (Case Study in Magepanda District) is 8.9% while 91.1% is influenced by other factors outside the research variables.